Effects of Different Processed Products of Polygonum multiflorum on the Liver. (9th March 2020) - Li, Ruo-Lan; Gao, Feng; Yan, Shu-Ting; Ou, Li; Li, Ming; Chen, Lin; Wei, Pei-Feng; Gao, Zong-Qiang
Abstract : Objective . Based on in vitro and in vivo experimental studies, the changes of the main components of Polygonum multiflorum and different processed products and their effects on hepatotoxicity were investigated. Methods . The components of different processed products of Polygonum multiflorum were determined by HPLC. The effects of processed products of different processing time periods on HepG2 cells were detected by using cell count kit-8 and the apoptosis method; the effects of different processed products on the mouse liver were detected by reverse transcription polymerase chain reaction and immunohistochemistry. Results . With the extension of processing time, the contents of various chemical components in Polygonum multiflorum increased, while the content of stilbene glucoside decreased. The serum of Polygonum multiflorum group and different steaming time groups had obvious inhibitory effect on HepG2 cells. For normal mice, the toxicity of raw Polygonum multiflorum and processed products at different processing time periods had certain toxicity to liver and gradually decreased with the prolongation of processing time. For mice in the liver injury group, the therapeutic effect of raw Polygonum multiflorum and processed products at different processing time periods was not obvious, but there is a trend of treatment. Conclusion . The content of the main components in Radix Polygonum multiflorum can be affected by processing time; stilbene glycoside may be the main component leading to liver injury. The degree of liver injury caused by Radix Polygonum multiflorum is negatively correlated with processing time.